Application of Experimental Methods in Science Learning to Improve Early Childhood Thinking Skills - Sapia, Sapia; Herlina, Herlina; Bachtiar, Muhammad Yusri; Wahira, Wahira (Pancasila International Journal of Applied Social Science, 2025)
This study aims to: 1) provide a description of the application of experimental methods in science learning to improve early childhood thinking skills; 2) knowing  the  Supporting Factors and Inhibiting Factors in the Application of Experimental Methods in Science Learning to Improve Early Childhood Thinking Skills. The research subjects consisted of three information people, namely 2 teachers and 1 principal. The experimental method was chosen because it is considered to be able to provide direct experience that stimulates children's active involvement in learning, so that it can increase their understanding of science concepts in depth. This study uses a qualitative descriptive approach, collecting data through observation, interviews, and documentation. The results of the study show that the application of experimental methods in science learning is able to improve the ability to think critically, logically, and creatively in early childhood. The main supporting factors for the success of this method are the availability of adequate facilities and infrastructure, as well as the active involvement of teachers as facilitators. The obstacles faced include a lack of time in implementing the experiment and limited teachers' understanding of the use of this method.